AN ANALYTICAL FORMULATION WITH ILL-CONDITIONED NUMERICAL SCHEME AND ITS REMEDY: SCATTERING BY TWO CIRCULAR IMPEDANCE CYLINDERS [2] - Sever, Emrah; Dikmen, Fatih; Suvorova, Olga A.; Tuchkin, Yury A. (IEEE, 2013)
The regularization of the well-known analytical formulation of the monochromatic electromagnetic wave scattering problem from two neighbor impedance circular cylinder system is presented. It is the improvement and extension of the work done for scattering from two perfectly conducting circular cylinders. Numerical results show that it is numerically much safer to solve the obtained infinite algebraic system at a lower truncation number also by ensuring the reliability of the solution.
10th International Conference on Electronics, Computer and Computation (ICECCO) -- NOV 07-09, 2013 -- Turgut Ozal Univ, Ankara, TURKEY
Keywords: Numerical stability; impedance; scattering; regularization; electromagnetics